1976
DOI: 10.1007/bf00582875
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the geneuvrB is indispensable for a polymerase I deficient strain ofEscherichia coli K-12

Abstract: Conclusive evidence in presented to show that the gene uvrA is dispensable, but the uvrB is indispensable for an Escherichia coli strain carrying gene polA1. We constructed strains E139 (sup-126 polAl uvrB59) and E159 (sup-126 polAl uvrA43) where mutations polAl, uvrB59 and uvrA43 are amber mutations and mutation sup-126 is an amber suppressor mutation effective at 30 degrees C but not at 42 degrees C. At 42 degrees C, strain E139 is inviable but strain E159 viable whereas both are viable at 30 degrees C. Reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…More than 25 years ago it was proposed that UvrB and UvrD might also be involved in DNA replication, since in vivo in the absence of DNA damage-inducing treatments, uvrB or uvrD mutations were found to be lethal in combination with a mutation in the polA gene (11,29,38,39). Combining a deletion of the uvrB gene with either a polA1 or a polA12 mutation leads to inviability (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 25 years ago it was proposed that UvrB and UvrD might also be involved in DNA replication, since in vivo in the absence of DNA damage-inducing treatments, uvrB or uvrD mutations were found to be lethal in combination with a mutation in the polA gene (11,29,38,39). Combining a deletion of the uvrB gene with either a polA1 or a polA12 mutation leads to inviability (38).…”
mentioning
confidence: 99%
“…Two different unidentified point mutations in uvrD are also lethal in combination with the polA1 mutation, indicating a role for UvrD in replication as well (11,39). In contrast with uvrB and uvrD, strains with point mutations in uvrA or uvrC (18,25,29,37) in a polA mutant background have been reported to be viable, although the plating efficiency of a uvrA6 polA12 strain was found to be reduced at 42°C (18,37).…”
mentioning
confidence: 99%
“…Because both recB (13) and uvrB (14) mutations are also lethal when Poll is deficient, we constructed recB poUA12 and uvrB poUL12 double mutants and found that their unconditional inviabilities at 42°C were not alleviated by this plasmid. These negative results could mean either that overproduction of (6) and has been demonstrated with our strain, SC18-12 (16).…”
mentioning
confidence: 99%
“…It is likely that the 3'->5' exonuclease activity becomes pivotal when the SOS response is constitutively turned on, because polA 1 inactivates both polymerization and 3'-*5' exonuclease activities whereas poLA25::miniTnl0spc appears to impair polymerization activity only (4). recB and uvrB mutations are also lethal when combined with a defectivepoL4 gene (24,25). Whether these lethal combinations are also suppressed by the lexA(Def) mutation remains to be seen.…”
Section: Discussionmentioning
confidence: 99%